Post-Translational Modifications of FXR; Implications for Cholestasis and Obesity-Related Disorders - Appelman, Monique D.; van der Veen, Suzanne W.; van Mil, Saskia W. C. (Frontiers in Endocrinology, 2021)
The Farnesoid X receptor (FXR) is a nuclear receptor which is activated by bile acids. Bile acids function in solubilization of dietary fats and vitamins in the intestine. In addition, bile acids have been increasingly recognized to act as signaling molecules involved in energy metabolism pathways, amongst others via activating FXR. Upon activation by bile acids, FXR controls the expression of many genes involved in bile acid, lipid, glucose and amino acid metabolism. An inability to properly use and store energy substrates may predispose to metabolic disorders, such as obesity, diabetes, cholestasis and non-alcoholic fatty liver disease. These diseases arise through a complex interplay between genetics, environment and nutrition. Due to its function in metabolism, FXR is an attractive treatment target for these disorders. The regulation of FXR expression and activity occurs both at the transcriptional and at the post-transcriptional level. It has been shown that FXR can be phosphorylated, SUMOylated and acetylated, amongst other modifications, and that these modifications have functional consequences for DNA and ligand binding, heterodimerization and subcellular localization of FXR. In addition, these post-translational modifications may selectively increase or decrease transcription of certain target genes. In this review, we provide an overview of the posttranslational modifications of FXR and discuss their potential involvement in cholestatic and metabolic disorders.